The management bible - Nelson, Bob, 1956- (John Wiley & Sons, 2005)
Are you a manager? You need your best friend-and secret weapon -- The Management Bible. The most comprehensive book on the topic of management available anywhere, this book offers in-depth coverage of the entire range of essential topics for today's managers and supervisors -- from beginners to seasoned veterans.